CONSTRUCTIONS OF DEVICES OF PROTECTION OF A HUMAN BODY FROM ELECTROMAGNETIC RADIATION - T. V. Borbotko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Constructions of devices of protection of the person from electromagnetic radiations on the basis of cappilary-porous or powdery materials are developed. Possibility of their use for decrease in electromagnetic radiations of the equipment of cellular communication and personal computers is shown.